TINJAUAN KEBUTUHAN TENAGA DI UNIT REKAM MEDIS RUMAH SAKIT UMUM UNIVERSITAS KRISTEN INDONESIA - Meliana; Hudiyati Agustini; Alivia Yuli Andini (APIKES Bhumi Husada Jakarta, 2022)
ABSTRACT This study was conducted to determine the need for medical recorders and health information at the Medical Record Unit of the Indonesian Christian University General Hospital. By using the Health Workload Analysis method and data collection techniques by direct observation and distributing questionnaires conducted from May to July 2021. Medical Record is a file that contains records and documents about the patient's identity, examination, treatment, actions and other services that have been provided to patients. Organizing quality medical records requires qualified health personnel and in accordance with their competencies. A good workforce will greatly affect the quality of service in the medical record work unit. The quality of service is related to the workload, so the workload must be in accordance with the number of personnel so that the service becomes quality. Based on the results of the research on the calculation of HRK needs using the Health Workload Analysis (ABK-Kes) method, it was found that the current required workforce is 10 people with the distribution of officers in each activity. Meanwhile, the number of staff available at this time is 9 people, therefore the Medical Record and Health Information Unit of the Indonesian Christian University General Hospital still requires an additional 1 person. Keywords : Manpower needs, medical records, Workload Analysis, ABK-Kes ABSTRAK Penelitian ini dilakukan untuk mengetahui jumlah kebutuhan tenaga Perekam Medis dan Informasi Kesehatan di Unit Rekam Medis Rumah Sakit Umum Universitas Kristen Indonesia. Dengan menggunakan metode Analisis Beban Kerja Kesehatan dan teknik pengumpulan data secara observasi langsung serta penyebaran kuesioner yang dilakukan pada bulan Mei sampai dengan Juli tahun 2021. Rekam Medis adalah berkas yang berisikan catatan dan dokumen tentang identitas pasien, pemeriksaan, pengobatan, tindakan dan pelayanan lain yang telah diberikan kepada pasien. Penyelenggaran rekam medis yang bermutu diperlukan tenaga kesehatan yang bermutu dan sesuai dengan kompetensinya. Tenaga kerja yang baik akan sangat mempengaruhi mutu pelayanan di unit kerja rekam medis. Mutu pelayanan berkaitan dengan beban kerja, maka beban kerja harus sesuai dengan jumlah tenaga agar pelayanan menjadi bermutu. Berdasarkan hasil penelitian perhitungan kebutuhan SDMK dengan metode Analisis Beban Kerja Kesehatan (ABK-Kes) didapatkan tenaga yang dibutuhkan saat ini adalah 10 orang dengan pembagian petugas dimasing-masing kegiatan. Sedangkan, jumlah tenaga yang tersedia saat ini adalah 9 orang, maka dari itu Unit Rekam Medis dan Informasi Kesehatan Rumah Sakit Umum Universitas Kristen Indonesia masih membutuhkan penambahan 1 orang tenaga. Kata Kunci : Kebutuhan tenaga kerja, Rekam Medis, Analisis Beban Kerja, ABK-Kes